Using AHP for Supplier Performance Assessment: A Case Study of SME in West Java - Yogi Sari, Oktora; A. Kosasih, Demas (International Journal of Psychosocial Rehabilitation, 2020)
A supplier is a source of fulfillment of production goods, which can directly affect the continuity of production because, without a supplier, the fulfillment of raw materials for production cannot be done and causes the cessation of production activities. Therefore, to meet the requirement of raw materials, a company requires supplier relationships that include involvement from the beginning in the decision, seriousness in cooperation, and mutual trust. With these, a good relationship will be established between the supplier and the company. Supplier selection is a difficult decision because various criteria must be considered in the decision-making process. The criteria used in this study are quality, price, delivery, and quality.